2020
DOI: 10.3389/fphar.2020.01267
|View full text |Cite
|
Sign up to set email alerts
|

Formulary Management Activities and Practice Implications Among Public Sector Hospital Pharmaceutical and Therapeutics Committees in a South African Province

Abstract: Introduction: The World Health Organization identified Pharmaceutical and Therapeutics Committees (PTCs) at district and hospital levels as one of the pivotal models to promote rational use of medicines (RUM). This is endorsed by the Government in South Africa. Formulary development and management is one of the main functions of PTCs. This study aimed to describe the formulary management activities among PTCs in public hospitals in Gauteng Province, South Africa, following initiatives to promote RUM in South A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 72 publications
0
26
0
Order By: Relevance
“…99 Examples include laws banning the dispensing of antibiotics in pharmacies without a prescription as well as national policies outlining the existence of DTCs in hospitals as currently seen in South Africa. 105 , 114 …”
Section: Methodsmentioning
confidence: 99%
“…99 Examples include laws banning the dispensing of antibiotics in pharmacies without a prescription as well as national policies outlining the existence of DTCs in hospitals as currently seen in South Africa. 105 , 114 …”
Section: Methodsmentioning
confidence: 99%
“…Odoch and colleagues found that domestic health changes such as the devolution of health services had influenced NML updates [ 16 ]. Implementation can be particularly challenging in decentralized health systems that enable autonomy for medicine selection and use within regions and hospitals, even when a national framework for essential medicines is in place [ 5 , 20 , 44 ]. Several studies described inconsistencies between NMLs and how they are implemented at a regional or hospital level at the discretion of local doctors [ 5 , 41 , 42 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…WHO recommends that all countries formulate and implement a comprehensive national medicines policy to improve access to safe and effective medicines of good quality [ 4 ]. A country’s NML is a government-approved list of medicines, which can often be adapted and implemented as a local formulary, or as a secondary list to the NML “tertiary list” [ 5 ]. The NML is intended to guide public sector procurement and supply, reimbursement schemes, medicine donations, and local production [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Pharmacists can also help in critical areas such as medication taking and adherence in ambulatory care, especially where health literacy is an issue, treat minor ailments and enhance appropriate prescribing and dispensing of antibiotics for infections such as upper respiratory tract infections (Abdulsalim et al, 2018;Rampamba et al, 2019;Godman et al, 2020a;Godman et al, 2020b;Ogunleye et al, 2020;Selvaraj et al, 2020). Besides, pharmacists in both hospitals and the community can promote pharmacovigilance activities, which is a concern in LMICs (Terblanche et al, 2017;Haines et al, 2020), as well as have a vital role as members of Drug and Therapeutic Committees (DTCs) guiding physicians and suggesting alternative treatments when there are shortages of medicines (Matlala et al, 2017;Terblanche et al, 2018;Matlala et al, 2020;Modisakeng et al, 2020). Consequently, this traditional relationship between physicians and pharmacists needs reassessing to enhance the effectiveness, safety, and adherence to medicines prescribed and dispensed.…”
Section: Introductionmentioning
confidence: 99%
“…In Australia, pharmacists are also providing consultative services to patients upon referral from their physicians (Tan et al, 2014), and in the United States of America, pharmacists are part of multidisciplinary teams in intensive care units enhancing patient outcomes (Preslaski et al, 2013). This is changing as seen in South Africa with their increasing role in DTC and other activities (Matlala et al, 2017;Terblanche et al, 2018;Matlala et al, 2020;Modisakeng et al, 2020) and in Kenya where hospital pharmacists are introducing new practices to improve the administration of oncology medicines (Kurgat et al, 2020).…”
Section: Introductionmentioning
confidence: 99%